BN‐Enabled Epitaxy of Pb1–xSnxSe Nanoplates on SiO2/Si for High‐Performance Mid‐Infrared Detection. Issue 40 (25th August 2015) - Wang, Qisheng; Wen, Yao; Yao, Fengrui; Huang, Yun; Wang, Zhenxing; Li, Molin; Zhan, Xueying; Xu, Kai; Wang, Fengmei; Wang, Feng; Li, Jie; Liu, Kaihui; et al.
<x xml:space="preserve">Abstract</x> By designing a few‐layer boron nitried (BN) buffer layer, topological crystalline insulator Pb1–xSnxSe nanoplates are directly grown on SiO2/Si, which shows high compatibility with current Si‐based integrated circuit technology. Back‐gated field‐effect transistors of Pb1–xSnxSe nanoplates exhibit a room‐temperature carrier mobility of 0.73–4.90 cm2 V−1 s−1, comparable to layered materials and molecular crystals, and high‐efficiency mid‐IR detection (1.9–2.0 μm).